On the Use of Embedded Fiber Optic Sensors for Measuring Early-Age Strains in Concrete - K.K. Santos Silva; F.A.N. Silva; T. Mahfoud; A. Khelidj; A. Brientin; A.C. Azevedo; J.M.P.Q. Delgado; A.G. Barbosa de Lima (Sensors, 2021)
Detailed information about concrete behavior in real structures is an important issue in controlling its performance during its service life, and the use of embedded sensors to obtain desired information such as temperature, onset of the cracking process and evolution of strains, has gained the attention of the building concrete industry. Data obtained using this technology can provide valuable information for decision making about the need for corrective interventions that can ensure the integrity and safety of concrete structures for long period of time. This paper presents a review of the current state-of-the-art of embedded fiber optic sensors used to assess concrete information of a wide range of aspects, comprising: existing alternative technologies, characteristics and advantages, practical applications and future developments. Complementarily, the work presents preliminary results of the use of fiber optic sensors to automatically and continuously perform expansion readings of AAR in concrete elements that facilitate both the storage—with elimination of the usual interruptions for manual readings—and the availability of continuous results of expansion data that are not possible to obtain with usual AAR tests code reading recommendations.